Stochastic behaviour of a two-unit system with two types of repairman and subject to random inspection - Tuteja, R.K.; Arora, R.T.; Taneja, Gulshan (Microelectronics and reliability, 1991)
Stochastic behaviour of a two-unit cold standby redundant system, with two types of repairman and subject to random inspection is studied. One repairman is “regular”; he always remains with the system and plays the dual role of inspection and repair. An expert repairman is called if the regular repairman is unable to do the job within some fixed time, or on system failure, whichever is earlier. Techniques of semi-Markov processes and regenerative processes have been used to obtain various measures of system effectiveness and profit incurred. Optimal policies for calling the expert repairman and maximum profit have been analysed, and some graphs are given.